(untitled) (Proceedings of Voronezh State University. Series: Geology, 2023)
Introduction: The petrogenesis of high-magnesium granitoids remain debated. The crystallization conditions these magmas have been poorly studied. Methodology: Mineralogical, chemical and isotopic studies of the Paleoproterozoic Novaya Melovatka pluton of high-magnesium granitites were carried out to decipher the crystallization conditions. Results and discussion: The pluton is composed of biotite-orthopyroxene quartz dioritic and monzodioritic porphyrites (Phase 1) and medium-grained biotite-amphibole quartz diorite, tonalite and granodiorite (Phase 2) containing and commingled Phase 1 mafic magmatic enclaves. Computations based on mineral and rock composition show that the parental magmas of the Phase 1 were water-poor (less than 3 wt. % dissolved H2O), with crystallization temperatures in the range 902–720°C. The parental magmas of the Phase 2 were water-rich (more than 6 wt. % dissolved H2O), with crystallization temperatures in the range 820–716°C. The suite crystallized at fO2 between NNO and NNO +1. Geobarometry (aluminium-in-hornblende) indicates crystallization at upper-crustal depths (i.e. 1.7–2.4 kbar). The maximum pressure was obtained from brown amphibole cores of the Phase 2 and relict amphibole crystals of the mafic xenoliths (up to 7.8 kbar). The Rb-Sr ages of mineral fractions and whole rock compositions were estimated: 202118 Ma (Phase 1) and 199418 Ma (Phase 2). Conclusion: The two parental melts (phases) of high-magnesium rocks of the Novaya Melovatka pluton crystallized at the same oxygen fugacity, but under different temperatures and water content at the upper crustal level. The brown amphibole were inherited from mafic-ultramafic lower crustal source. The Rb-Sr isochrons are interpreted as a result of secondary recrystallization of the rocks due to lithosphere reactivation by distant stresses.